Global, regional, and national burden of motor neuron disease in adults aged 65 years and older from 1990 to 2021 and forecast to 2040 - Zhao, Quanfeng; Zhang, Bin; Chen, Xiulan; Fu, Peishu; Yang, Yang; Wang, Qian (Frontiers in Neurology, 2025)
AimGiven the significant social burden of motor neuron disease (MND) among elderly patients (aged ≥ 65 years) and the lack of detailed research on its epidemiological characteristics, this study aims to elucidate the temporal trends and distributional characteristics of MND in the elderly from 1990 to 2021, as well as to forecast its future burden.MethodsThe age-standardized rates (ASR) and absolute numbers of MND-related incident, prevalent, death, and disability-adjusted life years (DALYs) among older patients (aged ≥ 65 years) globally were derived from the Global Burden of Disease (GBD) study from 1990 to 2021. The data were derived by gender, age group and geographic region. An estimated annual percentage change (EAPC) was estimated to represent temporal trends, and a Bayesian Age-Period-Cohort model was used to forecast the future burden of elderly MND.ResultsIn 2021, the global ASRs of incidence, prevalence, mortality, and DALYs for elderly MND were 3.63 (95% uncertainty intervals [UI], 2.95–4.36), 11.45 (95% UI, 8.69–14.88), 3.28(95% UI, 2.90–3.61), and 59.92 (95% UI, 53.94–65.53), respectively. Elderly patients those were from high socio-demographic index (SDI) region, as well as males, exhibited the highest burden. From 1990 to 2021, the global ASRs of elderly MND increased, with EAPCs of 0.43 (95% confidence interval [CI], 0.38–0.49), 0.58 (95% CI, 0.48–0.68), 0.90 (95%CI, 0.75–1.06), and 0.84 (95% CI, 0.71–0.96), respectively. Positive correlations were found between sociodemographic index and the burden of elderly MND. Health inequalities were evident across 204 countries and regions, with the inequality slope index raised from 23.46 (95% CI: 18.52–28.40) in 1990 to 80.70 (95% CI: 65.07–96.32) in 2021. Compared to the figures observed in 2021, our forecasts indicate a continued rise in the burden of elderly MND up to 2040, with the projected ASIR expected to reach 3.15 (95% UI, 2.28–4.01) and the ASMR anticipated to be 3.32 (95% UI, 2.11–4.55).ConclusionThe burden of MND among elderly patients is substantial, particularly in high SDI region and among males. From 1990 to 2021, the global burden of elderly MND has exhibited an increasing trend. The burden of elderly MND varies significantly across the world, necessitating more targeted screening strategies and preventive measures to address the issue of elderly MND.